Consumer credit: report of the Committee - Great Britain; Crowther, Geoffrey (London: H.M.S.O., 1971)
This reports examines the problem associated with the consumer credit law and practice in long, medium and short-term, including it implications on goods and services
This is a committee's report.
Includes bibliographical references
mf 22/01/2019
Loans
Keywords: Consumer credit